Recommendations for a safe restart of elective aerosol-generating oral surgery procedures following the COVID-19 pandemic outbreak: An Italian multicenter study. Issue 5 (May 2022) - Giovanditto, Federica; Soma, Damiano; Vaira, Luigi Angelo; Pispero, Alberto; Lombardi, Niccolò; Ristoldo, Federico; Mariani, Umberto; Pizzi, Silvia; Isola, Antonio; Smania, Pierantonio; Albanese, Massimo; D'Agostino, Antonio; et al.
Abstract: Among healthcare workers, oral and maxillofacial surgeons are some of the most exposed to coronavirus disease (COVID-19). The aim of this retrospective study was to develop suggestions for continuing the work of oral and maxillofacial surgeons using a safe protocol for elective and urgent aerosol-generating procedures that could prevent the onset of new clusters. Based on the results obtained and a guidelines review of those Asian countries that had promptly managed the current pandemic, the following safety protocol was developed: